KAJIAN TENTANG PREVALENSI KONTRASEPSI KELUARGA BERENCANA CATATAN KECIL DALAM UPAYA PENCAPAIAN MDGs 2015 DI MALUKU - P. ADAM, FELECIA (PIRAMIDA; Vol. 7, No. 2 Desember 2011)
Some population indicatores that were reported by Indonesia Demographic and HealthSurvey in the year 2007 gave an apprehensive illustration about the population development inMoluccas, such as total fertility rate 3.7, contraceptive prevalence rate 34 percent, andunmetneed reached 22 percent. These three indicators were interaction and gave contribution tothe others.The objective of this study was to obtain the illustration of the low of contraceptiveprevalence rate of current user, because this indicator was very significant in achieving MDGs inMoluccas, especially for the fifth goal.This study was using the main data from Indonesia Demographic and Health Survey inthe year 2007. The findng of this study that the low of the contraceptive prevalence rate ofcurrent user in Moluccas can be caused by some factors as well as : the low educated of women,the high birth rate of adolescent, the coverage of uncontrolled pregnancy health care, thetendency of current users to choose a low effective contraception, the high rate of unmetneed,the high rate of poverty, a hard to find contraception, a hard accesibility related to geographicfactors which too much islands.
Keywords: contraceptive prevalence rate, current user, MDGs